Urgensi Perda Penanggulangan Wabah Menular di Kota Yogyakarta: The Urgency of Local Regulations for Overcoming Infectious Outbreaks in Yogyakarta City - As-Shidiq, Abdullah Widy; Reza, M. Hilmi Miftahzen; Wafi, Muhammad Syafiq (Seminar Nasional Hukum Universitas Negeri Semarang, 2021)
The research on " Urgency of Regional Regulations for Handling Infectious Outbreaks in the City of Yogyakarta " is interesting to study because it is based on Government Regulation No. 40 of 1991 on Handling infectious epidemics which mandates that regional heads are responsible for technical implementation of epidemic control in regions . one of the prevention efforts in the region is to create a legal basis of controlling infectious diseases in the city of Yogyakarta as a guideline on implementing Disease Prevention and Control in Yogyakarta. The purpose of this study was to determine the urgency of making a regional regulation to control infectious epidemics as a prevention effort in / into / of the people in Yogyakarta. The scope of our study is the regulation of local regulations related to citizens constitutional rights. The literature review used to analyze this problem is the guarantee and protection for / against human rights and responsive legal theory . The research method used is a normative juridical approach from / to a statutory approach, a conceptual approach and a comparative approach. The results of the study show the basis of the formation of a regional regulation on infectious disease prevention in Yogyakarta from a philosophical , sociological and juridical perspective.